CesRK, a Two-Component Signal Transduction System in Listeria monocytogenes, Responds to the Presence of Cell Wall-Acting Antibiotics and Affects β-Lactam Resistance - Kallipolitis, Birgitte H. (American Society for Microbiology, 2003)
Listeria monocytogenes is a food-borne pathogen that can cause a variety of illnesses ranging from gastroenteritis to life-threatening septicemia. The β-lactam antibiotic ampicillin remains the drug of choice for the treatment of listeriosis. We have previously identified a response regulator of a putative two-component signal transduction system that plays a role in the virulence and ethanol tolerance of L. monocytogenes. Here we present evidence that the response regulator, CesR, and a histidine protein kinase, CesK, which is encoded by the gene downstream from cesR, are involved in the ability of L. monocytogenes to tolerate ethanol and cell wall-acting antibiotics of the β-lactam family. Furthermore, CesRK controls the expression of a putative extracellular peptide encoded by the orf2420 gene, located immediately downstream from cesRK. Inactivation of orf2420 revealed that it contributes to ethanol tolerance and pathogenesis in mice. Interestingly, we found that transcription of orf2420 was strongly induced by subinhibitory concentrations of various cell wall-acting antibiotics, ethanol, and lysozyme. The induction of orf2420 expression was abolished in the absence of CesRK. Our data suggest that CesRK is involved in regulating aspects of the cell envelope architecture and that changes in cell wall integrity provide a potent stimulus for CesRK-mediated regulation. These results further our understanding of how L. monocytogenes senses and responds to antibiotics that are used therapeutically in the treatment of infectious diseases.